Makna Pengalaman Interaksi Komunikasi Lintas Budaya pada Pengajar Indonesia dan Murid Internasional The Independent Swimming School - Nida Aulia Isnaini Azhar; Erik Setiawan (UNISBA Press, 2024)
Abstract. This research was conducted based on the phenomenon of Indonesian teachers experiencing cross-cultural communication with international students. The aim of this research is to understand the experiences of cross-cultural communication interactions experienced by Indonesian teachers with international students, as well as to identify the benefits and obstacles that arise in this process. The data in this research was obtained through in-depth interviews with research subjects, namely five people consisting of one teacher from Indonesia and four students from Ukraine, Italy, Hong Kong and Switzerland. This research method uses qualitative with a phenomenological study approach. Data collection techniques use observation, interviews and documentation. In data analysis, researchers used three technical patterns of data analysis according to Miles and Huberman, namely Data Reduction, Data Presentation, and Drawing conclusions. Based on this phenomenon, the problem in this research is formulated as follows: (1) What are the motives of Indonesian teachers and international students at The Independent Swimming School? (2) How does the experience of interaction in cross-cultural communication affect the lives of Indonesian teachers and international students at The Independent Swimming School? (3) What is the meaning of interaction in cross-cultural communication for Indonesian teachers and international students at The Independent Swimming School? The research results show that the main motives underlying teaching include a focus on cultural interaction, increasing self-confidence, and quality teaching systems. Cross-cultural communication interactions are influenced by environmental conditions, language skills, and understanding of culture, providing a more meaningful experience for Indonesian teachers in dealing with international students at The Independent Swimming School. Abstrak. Penelitian ini dilakukan berdasarkan adanya fenomena mengenai pengajar Indonesia yang mengalami komunikasi lintas budaya dengan murid Internasional. Tujuan penelitian ini adalah untuk memahami pengalaman interaksi komunikasi lintas budaya yang dialami oleh pengajar Indonesia dengan murid internasional, serta untuk mengidentifikasi manfaat dan hambatan yang muncul dalam proses tersebut. Data-data dalam penelitian ini diperoleh melalui wawancara mendalam dengan subjek penelitian, yaitu lima orang yang terdiri dari satu pengajar asal Indonesia dan empat orang murid dari negara Ukraina, Italy, Hongkong, dan Swiss. Metode penelitian ini menggunakan kualitatif dengan pendekatan studi Fenomenologi. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Dalam analisis data peneliti menggunakan tiga pola teknis analisis data menurut Miles dan Huberman yaitu Reduksi Data, Penyajian Data, dan Menarik kesimpulan. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Apa motif pengajar Indonesia dan murid Internasional The Independent Swimming School? (2) Bagaimana pengalaman interaksi dalam komunikasi lintas budaya terhadap kehidupan pengajar Indonesia dan murid Internasional The Independent Swimming School?(3) Bagaimana makna interaksi dalam komunikasi lintas budaya terhadap pengajar Indonesia dan murid Internasional The Independent Swimming School?. Hasil penelitian menunjukkan bahwa motif utama yang mendasari pengajaran meliputi fokus pada interaksi budaya, peningkatan percaya diri, dan sistem pengajaran berkualitas. Interaksi komunikasi lintas budaya dipengaruhi oleh kondisi lingkungan, kemampuan bahasa, dan pemahaman terhadap budaya memberikan pengalaman yang lebih bermakna bagi pengajar Indonesia dalam menghadapi murid internasional di The Independent Swimming School.